UJI PENGARUH PRAKTIK AUDIT TERHADAP INTEGRITAS LAPORAN KEUANGAN DENGAN MODERASI FEE AUDIT (Studi Empiris Pada Perusahaan Manufaktur Sektor Industri Dasar Dan Kimia Yang Terdaftar Di BEI Tahun 2014-2016)’’ - Dinda Niagara Ermaja; Emrinaldi Nur DP; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this study is to examine the influence of auditor switching, audit delay, and audit timeliness to integrity of financial statement with fee audit as a moderating variable. This research use auditor switching, audit delay, and audit timeliness as independent variable. Dependent variable in this research is integrity of financial statement and fee audit as a moderating variable. Data used in this research are collected from financial statement of manufacturing companies listed in IDX. The population of this research comprise of manufacturing companies basic and chemical industry sector, listed in Bursa Efek Indonesia during the period of 2014-2016 a total of 32 companies with 96 unit of samples. The samples are determined using purposive sampling method. Analysis of data is carried out using logistic regression method and moderated regression analysis with the aid of SPSS version 21 computer program.The results of hypotesis testing showed that auditor switching and audit delay have an influence to integrity of financial statement. But,audit timeliness does not have an influence to integrity of financial statement. Auditor switching and audit delay have influence to integrity of financial statement with fee audit as a moderating. But, audit timeliness does not have influence to integrity of financial statement with fee audit as a moderating.Keywords : Auditor switching, audit delay, audit timeliness, fee audit, and integrity of financial statement